Strategic atrocities: civilians under crossfire - theory and evidence from Colombia (2016)
Armed actors in civil war often target civilians to create fear and punish allegiance with the enemy. This strategy secures collaboration with the perpetrator, strengthening its civilian support, and helps the consolidation of territorial supremacy over contested regions. In this chapter, I illustrate this strategic use of atrocities with a model involving two armed groups who fight over territorial control and who try to secure compliance of local civilians through a combination of carrots and sticks. I study the conditions that lead to more or less civilians killed and illustrate the main theoretical arguments with descriptive evidence from the recent history of Colombia’s civil war.